Coenzyme Q10 dose-escalation study in hemodialysis patients: safety, tolerability, and effect on oxidative stress. Issue 1 (December 2015) - Yeung, Catherine; Billings, Frederic; Claessens, Adam; Roshanravan, Baback; Linke, Lori; Sundell, Mary; Ahmad, Suhail; Shao, Baohai; Shen, Danny; Ikizler, T.; Himmelfarb, Jonathan
Abstract Background Coenzyme Q10 (CoQ10 ) supplementation improves mitochondrial coupling of respiration to oxidative phosphorylation, decreases superoxide production in endothelial cells, and may improve functional cardiac capacity in patients with congestive heart failure. There are no studies evaluating the safety, tolerability and efficacy of varying doses of CoQ10 in chronic hemodialysis patients, a population subject to increased oxidative stress. Methods We performed a dose escalation study to test the hypothesis that CoQ10 therapy is safe, well-tolerated, and improves biomarkers of oxidative stress in patients receiving hemodialysis therapy. Plasma concentrations of F2 -isoprostanes and isofurans were measured to assess systemic oxidative stress and plasma CoQ10 concentrations were measured to determine dose, concentration and response relationships. Results Fifteen of the 20 subjects completed the entire dose escalation sequence. Mean CoQ10 levels increased in a linear fashion from 704 ± 286 ng/mL at baseline to 4033 ± 1637 ng/mL, and plasma isofuran concentrations decreased from 141 ± 67.5 pg/mL at baseline to 72.2 ± 37.5 pg/mL at the completion of the study (P  = 0.003 vs. baseline andP  < 0.001 for the effect of dose escalation on isofurans). Plasma F2 -isoprostane concentrations did not change during the study. Conclusions CoQ10 supplementation at doses as high as 1800 mg per day was safe in all subjects and well-tolerated in most. Short-term daily CoQ10 supplementation decreased plasma isofuran concentrations in a dose dependent manner. CoQ10 supplementation may improve mitochondrial function and decrease oxidative stress in patients receiving hemodialysis. Trial Registration This clinical trial was registered on clinicaltrials.gov [NCT00908297 ] on May 21, 2009.